2020
DOI: 10.1002/lt.25668
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ Liver Machine Perfusion: The Impact of Fresh Frozen Plasma

Abstract: The primary aim of this single-center, phase 1 exploratory study was to investigate the safety, feasibility, and impact on intrahepatic hemodynamics of a fresh frozen plasma (FFP)-based perfusate in ex situ liver normothermic machine perfusion (NMP) preservation. Using an institutionally developed perfusion device, 21 livers (13 donations after brain death and 8 donations after circulatory death) were perfused for 3 hours 21 minutes to 7 hours 52 minutes and successfully transplanted. Outcomes were compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Briefly, Initial literature searches identified 1,289 publications. After excluding ineligible publications based on the selection and exclusion criteria, 12 studies, including 10 nonrandomized prospective phase I clinical trials (10,(21)(22)(23)(24)(25)(26)(27)(28)(29), one multiinstitutional randomized study (18), and one single-center, randomized controlled study (30), were eventually included in the meta-analysis of the comparison between MP and CS on clinical outcomes in LT. In the 12 included studies, five studies used hypothermic machine perfusion (HMP), whereas the other seven studies investigated normothermic machine perfusion (NMP).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, Initial literature searches identified 1,289 publications. After excluding ineligible publications based on the selection and exclusion criteria, 12 studies, including 10 nonrandomized prospective phase I clinical trials (10,(21)(22)(23)(24)(25)(26)(27)(28)(29), one multiinstitutional randomized study (18), and one single-center, randomized controlled study (30), were eventually included in the meta-analysis of the comparison between MP and CS on clinical outcomes in LT. In the 12 included studies, five studies used hypothermic machine perfusion (HMP), whereas the other seven studies investigated normothermic machine perfusion (NMP).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…As shown in Table 2, all 12 included studies reported posttransplant peak ALT and/or AST level within 1 week. Seven of the 12 included studies found a significantly lower posttransplant peak ALT and/or AST level during the first 7 days after surgery in the MP group compared with the CS group (P < 0.05) (10,18,21,22,25,26,28), whereas the rest (five studies) observed comparable hepatic transaminases levels between two groups (23,24,27,29,30). However, different studies reported transaminase by different data types and at variable time points.…”
Section: Meta-analysis Of Primary Outcomesmentioning
confidence: 98%
“…To do this, NMP requires the use of oxygenators and the presence of oxygen transporters in the perfusate, with human red blood cells being the most common oxygen transporter used in current protocols. [45][46][47][48][49][50] Unlike the HMP configuration, in NMP protocols, liver grafts are normally dually perfused through the portal vein and the hepatic artery. The maintenance of the organ metabolic activity during NMP offers the possibility to assess organ viability by measuring many metabolic parameters, such as lactate clearance, pH and glycemic levels, as well as bile production and its constitution.…”
Section: Normothermic Machine Perfusionmentioning
confidence: 99%
“…Using a noncommercial custom-made perfusion device, Liu et al compared the outcome of 21 LT performed with NMP-preserved livers to a historical series of LT performed with livers preserved by SCS in a 1:4 ratio. The NMP group presented less EAD, no cases of biliary complications, and the only death in this group was due to a cerebral vascular accident 8 months after LT. 50 Recently, Jassem et al reanalyzed liver tissue samples and hepatic mononuclear cells collected from DBD livers transplanted after NMP and initially published by Ravikumar et al They observed that NMP changed the gene expression profile from proinflammation to prohealing and regeneration compared with SCS liver samples. In addition, they observed a reduction in the population of T cells that produce inflammatory factors and an increase in the pool of regulatory T cells in NMP livers.…”
Section: Prospective Clinical Studies Using Normothermic Machine Perfmentioning
confidence: 99%
See 1 more Smart Citation